Empirical manipulation of the thermoinactivation kinetics of Bacillus amyloliquefaciens and Bacillus licheniformis α-amylases for thermal process evaluations. (December 2016) - Luo, Zijun; Tucker, Gary; Brown, Helen
Abstract: In an attempt to obtain more accurate and stable time and temperature integrators (TTIs) for the evaluation of commercial pasteurisation process, the thermoinactivation kinetics (D and z value) of amylases contained in the TTIs from two sources, Bacillus amyloliquefaciens (BAA) and Bacillus licheniformis (BLA) were determined under different TTI conditions ( i.e ., pH, Ca 2+, and enzyme concentration). Under 21 different TTI conditions tested for BAA, D70 value is found to vary from 5.9 to 159.9 min, D85 value vary from 4.5 to 40.5 min, and z value vary from 6.2 to 30.4°C, respectively; Under 14 different TTI conditions tested for BLA, D90 value is found to vary from 2.5 to 9.9 min, and z value vary from 9.3 to 17.4°C, respectively. The thermoinactivation kinetics of TTI has been successfully modified to match the thermoinactivation kinetics of target microorganisms in commercial mild pasteurisation processes through these manipulations. We believe this empirical approach of manipulation has provided practical data and a better understanding of how to obtain desired thermoinactivation kinetics. This makes the enzymes and therefore TTIs better candidates for quantifying the thermal impact on both safety and quality parameters in commercial pasteurisation process. Industrial relevance: Quantification of the thermal process is of paramount importance to ensure the safety and quality of the heat-preserved food. Bacillus amylase-based time and temperature integrators (TTIs) have been developed as an alternative tool for thermal process evaluations in food industries, where conventional thermal sensors can not apply. Based on the results of this study, it is possible to manipulate the thermoinactivation kinetics of both Bacillus amyloliquefaciens and Bacillus licheniformis amylases to match the thermoinactivation kinetics of the target microorganisms in commercial pasteurisation process. Manipulation of the D and z value may be required when the supplied enzyme batch changes. The ability to undertake this manipulation contributes significantly to producing more accurate and consistent time and temperature integrators for its commercial use ( e.g ., thermal process validation). Moreover, being able to manipulate amylase activity to achieve target D and z values may also make it a potential candidate for the development of TTIs to monitor quality and nutritional markers. Consequently, TTIs can be developed to quantify the thermal impact on quality and nutritional parameters in pasteurised products. Highlights: D and z value of two amylases under different levels of Ca 2 +, pH and concentration were studied. For Bacillus amyloliquefaciens amylase, obtained D70, D85 & z values ranged from 5.9 to 159.9 min, from 4.5 to 40.5 min, and from 6.2 to 30.4 °C, respectively For Bacillus licheniformis amylase, obtained D90 value ranged from 2.5 to 9.9 min, and z value ranged from 9.3 to 17.4 °C, respectively Differences in structures and inactivation mechanisms among amylases were discussed. Extrinsic manipulation of Bacillus amylase thermoresistance to a desired target was feasible.